Analysis of Numeracy Literacy Skills of Grade V Students in Solving Geometry Problems - Widiyawaty, Sakinah; Nurafni, Nurafni (Jurnal Inovasi Pendidikan Dasar, 2024)
This research aims to determine students' numeracy literacy abilities. This research includes descriptive analysis research with a qualitative approach. Data was collected through observation, tests, and interviews. The results of the research show that the numeracy literacy skills of 26 class V students at SDN Sugutamu are in the low category with an average score of 32. There are 2 students in the high category, 7 students in the medium category, and 17 students in the low category. Numeracy literacy indicators are not fulfilled due to student errors including 1) Not writing down aspects that are known and asked about in the question, 2) Not writing down the steps for completing the question, 3) The picture made does not match the question instructions, 4) Errors in determining the results of arithmetic operations, 5) Do not state decisions taken based on the answers obtained.